2019
DOI: 10.1002/mds.27782
|View full text |Cite
|
Sign up to set email alerts
|

Antisense therapies for movement disorders

Abstract: Currently, few disease‐modifying therapies exist for degenerative movement disorders. Antisense oligonucleotides are small DNA oligonucleotides, usually encompassing ∼20 base pairs, that can potentially target any messenger RNA of interest. Antisense oligonucleotides often contain modifications to the phosphate backbone, the sugar moiety, and the nucleotide base. The development of antisense oligonucleotide therapies spinal muscular atrophy and Duchenne muscular dystrophy suggest potentially wide‐ranging thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 71 publications
(141 reference statements)
0
34
0
6
Order By: Relevance
“…ASOs are short synthetic oligonucleotides that can bind to pre-RNA through Watson-Crick base pairing and modulate pre-RNA splicing in the target gene bypassing the disease-causing mutation. Currently, several ASOs have received approval by the U.S. Food and Drug Administration for the therapy of neurological disorders (15). Our patient may also benefit from ASO-based therapy in the future who carry an ETFDH synonymous variant causing exon skipping.…”
Section: Discussionmentioning
confidence: 97%
“…ASOs are short synthetic oligonucleotides that can bind to pre-RNA through Watson-Crick base pairing and modulate pre-RNA splicing in the target gene bypassing the disease-causing mutation. Currently, several ASOs have received approval by the U.S. Food and Drug Administration for the therapy of neurological disorders (15). Our patient may also benefit from ASO-based therapy in the future who carry an ETFDH synonymous variant causing exon skipping.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown in laboratory-based assessments that measures of spatial and temporal movement variability allow distinctively to capture and characterize the specificities of ataxic gait [3][4][5][6][7][8][9][10] . Moreover, they allow to quantify disease severity even at preclinical stages of DCA 11,12 and to capture treatment-induced improvements in a fine-grained fashion [13][14][15] , thus suggesting a high potential as both progression and treatment response parameters in the upcoming treatment trials [16][17][18] . Recently, first studies showed that such measures of spatio-temporal variability characterizing ataxic gait can also be captured using wearable inertial sensors in clinical assessments 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Although much of the therapeutic research on diseases such as HD have attempted to discover ways for promoting the clearance of the abnormal proteins that cause neurodegeneration, none has yet been successful. Furthermore, while therapeutic development aimed at the degradation of abnormal mRNA using nucleic acid drugs—which have attracted attention in recent years—is progressing, and some technologies have advanced to the stage of clinical trials, 50 whether or not these drugs can be appropriately delivered to the central nervous system remains an open question. Amidst these events, the development of treatments that seek to modulate the length of abnormally expanded repeats—the more fundamental cause of repeat expansion disorders—has begun 51 .…”
Section: Repeat Length Modulation Therapymentioning
confidence: 99%